Analisis Pengawasan Inspektorat Daerah Terhadap Pelaksanaan E-Procurement Pada Pemerintah Provinsi Sulawesi Utara - ADA, YUSTINUS; KALANGI, LINTJE; WARONGAN, JESSY D.L (Universitas Sam Ratulangi, 2020)
Abstract. Inspectorate of North Sulawesi Province has a role to increase the effectiveness of E-Procurement implementation and to detect and prevent problems in the implementation of E-Procurement in the Regional Government of North Sulawesi Province. This study aims to analyze the implementation of supervision which has been carried out by the Regional Inspectorate of North Sulawesi Province as the Internal Government Supervisory Apparatus (APIP) in supporting the optimal functioning of E-Procurement in the Government of North Sulawesi Province. This is a qualitative research with a case study approach. Data were obtained by in-depth interviews, observation, and documentation study. The results show that (1) the supervision of the Regional Inspectorate on the implementation of E-Procurement in the North Sulawesi Provincial Government, has been conducted solely by Probity Audit activities and has not been yet implemented fully and effectively. It is because probity audits did not reach all work packages and were only carried out at certain stages of the process;(2) the Audit Work Program (PKA) are not accessed by the risk assessment process and SPSE upgrades are not accompanied by the socialization of the system to the Inspectorate as the Internal Government Supervisory Apparatus (APIP). These conditions occur due to several obstacles in the implementation of supervision. These constraints are (1) Not all auditors have the competencency skills to carry out an audit of E-Procurement, (2) the implementation of E-Procurement supervision has not been supported by the E-Procurement Audit Guideline, and (3) limited communications between the auditor and the auditee. In order to establish the effectiveness of the implementation of E-procurement: (1) Regional Inspectorate supervision are needed to improve auditor competencency, (2) the internal control system of the Regional Organization must be improved by carrying out socialization, technical guidance, and (3) improving the APIP supervision system with the use of supervision applications and the establishment of the E-Procurement Task Force.Keywords: Supervision, E-Procurement, Probity AuditAbstrak. Inspektorat Daerah Provinsi Sulawesi Utara berperan untuk meningkatkan efektivitas pelaksanaan E-Procurement serta mendeteksi dan mencegah timbulnya permasalahan dalam pelaksanaan E-Procurement pada Pemerintah Daerah Provinsi Sulawesi Utara. Penelitian ini bertujuan menganalisis pelaksanaan pengawasan yang telah dilaksanakan oleh Inspektorat Daerah Provinsi Sulawesi Utara selaku Aparat Pengawasan Intern Pemerintah (APIP) dalam mendukung optimalnya fungsi pelaksanaan E-Procurement pada Pemerintah Provinsi Sulawesi Utara. Penelitian ini adalah jenis penelitian kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara mendalam, observasi dan studi dokumentasi.Â Hasil penelitian menunjukkan bahwa (1) pengawasan Inspektorat Daerah atas pelaksanaanÂ E-Procurement di Pemerintah Provinsi Sulawesi Utara hanya melalui kegiatan Probity Audit dan belum sepenuhnya efektif, karena probity audit tidak menjangkau semua paket pekerjaan dan hanya dilakukan pada tahapan proses tertentu; (2) Program Kerja Audit (PKA) tidak melalui proses penilaian resiko dan upgrade SPSE tidak dibarengi dengan sosialisasi sistem kepada Inspektorat selaku Aparat Pengawasan Internal Pemerintah (APIP). Kondisi di atas terjadi karena adanya beberapa kendala dalam pelaksanaan pengawasan. Kendala-kendala tersebut yaitu (1) tidak semua auditor memiliki kompetensi untuk melaksanakan audit atas E-Procurement, (2) pelaksanaan pengawasan E-Procurement belum didukung dengan Pedoman Audit E-Procurement dan (3) komunikasi yang terbatas antara auditor dan auditee. Agar pengawasan Inspektorat Daerah menjadi efektif atas pelaksanaan E-Procurement maka diperlukan perbaikan yaitu (1) meningkatkan kompetensi auditor, (2) meningkatkan Sistem Pengendalian Internal Perangkat Daerah dengan cara pelaksanaan sosialisasi dan bimbingan teknis dan (3) meningkatkan sistem pengawasan APIP melalui penggunaan aplikasi pengawasan dan pembentukan Satgas E-Procurement.Kata Kunci: Pengawasan, E-Procurement, Probity Audit